Dietary Supplementation with Complex Enzymes and Tea Residue Improved the Production Efficiency of Xiangling Pigs - Runhua Yang; Yulian Li; Zhenyu Lei; Maisheng Wu; Hong Tan; Fang Liu; Yanmei Gong; Weijian Zhong; Jiayan He; Shujuan Zeng; Zhiyong Fan; Shusong Wu (Animals)
This study evaluated the effects of tea residue combined with complex enzymes on the growth performance, serum biochemistry, meat quality, and intestinal microbiota of Xiangling fattening pigs. A total of 120 healthy Xiangling fattening pigs, with an average weight of 47.93 kg (±15.28 kg), were randomly assigned to five treatment groups, each comprising four replicates of six pigs. The control group (CON) received a basal diet; the experimental groups received a diet containing 5.8% fermented tea residue as an alternative energy and protein source (dry matter basis) and mixed additional 0 (CZ), 200 (M200), 400 (M400), and 800 (M800) complex enzymes. The trial lasted for 83 days. The results showed that tea residue and complex enzymes failed to affect growth performance (p > 0.05). Tea residue reduced the serum aspartate aminotransferase and alkaline phosphatase activities (p < 0.01), and complex enzyme supplementation lowered the total cholesterol levels and reduced the alanine aminotransferase activity (p < 0.05). Additionally, tea residue decreased the pH24h and b*1h values (p < 0.05), and complex enzyme supplementation increased the L*24h value and pork shear force (p < 0.05). In terms of amino acid content, tea residue significantly elevated aspartic acid and inosine monophosphate (p < 0.05), and complex enzyme addition increased the glutamic acid, lysine, alanine, valine, tyrosine, isoleucine, leucine, and phenylalanine levels (p < 0.05). The 800 mg/kg complex enzyme group exhibited a reduction in the C10:0, C15:0, and C17:0 contents (p < 0.05). Microbial analysis showed that tea residue promoted the abundance of Oribacterium and Butyricicoccus, while enzyme supplementation enriched Eggerthellaceae, Oscillospirales, and Peptococcaceae. Overall, the combination of tea residue and complex enzymes improved the pork quality, enhanced metabolic health markers, and modulated the gut microbiota composition, with the 400 mg/kg enzyme dose (M400) achieving the most pronounced benefits. These findings suggest a potential feeding strategy for improving pork quality without compromising growth performance.